2020
DOI: 10.1002/csc2.20352
|View full text |Cite
|
Sign up to set email alerts
|

Silicon and selenium fertilizer management improved productivity and aroma of fragrant rice

Abstract: Both Si and Se are the nutrient elements which had significant effects on crop growth and development. However, the application of Si and Se fertilizer management in field production of fragrant rice (Oryza sativa L.) was rarely reported. The present study was conducted with the objective to explore the effects of Si and Se fertilizer on fragrant rice performance though a six-season field experiment. The Se rates were set at three levels: 0 g ha −1 (Se0), 36 g ha −1 (Se1), and 72 g ha −1 (Se2). The SiO 2 rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Reactive oxygen species (ROS) include substances, such as superoxide and peroxides, which create a chain reaction with unsaturated fatty acids in the cell membranes; thus, causing damage to the plant cells because the reactants destabilize the stable shape of the cell membranes [25]. Increasing the activity of antioxidant enzymes, including CAT, SOD, and POD, play an important role in suppressing extra ROS, thereby maintaining normal levels of these ROS [26].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) include substances, such as superoxide and peroxides, which create a chain reaction with unsaturated fatty acids in the cell membranes; thus, causing damage to the plant cells because the reactants destabilize the stable shape of the cell membranes [25]. Increasing the activity of antioxidant enzymes, including CAT, SOD, and POD, play an important role in suppressing extra ROS, thereby maintaining normal levels of these ROS [26].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Se, the application of silicon (Si) or manganese (Mn) fertilizer also increased the 2-AP levels and grain yield in fragrant rice. , Molybdenum (Mo) application also enhanced the 2-AP content in rice under Cd stress. , Not only the individual nutrients but also their coapplication and/or synergism also showed an increase in 2-AP contents. For example, a combination of Zn and lanthanum, Zn and Se, and Si and Se also led to an increase in grain 2-AP contents in fragrant rice. , …”
Section: Advancement In Agro-management Practices To Improve the Arom...mentioning
confidence: 99%
“…Previous studies revealed that the application of silicon fertilizer could increase the 2-AP content due to the improved PRO and net photosynthetic rates [9]. Du et al [10] showed that silicon and selenium fertilizer management regulated soil, increased photosynthesis, and promoted dry matter accumulation, which is beneficial for promoting the grain yield and 2-AP content of fragrant rice. Meanwhile, the application of nitrogen fertilizer could increase the 2-AP content through an increase in the PRO content [11].…”
Section: Introductionmentioning
confidence: 99%